2020
DOI: 10.3906/elk-1907-166
|View full text |Cite
|
Sign up to set email alerts
|

Detailed modeling of a thermoelectric generator for maximum power point tracking

Abstract: Thermoelectric generators (TEGs) are used in small power applications to generate electrical energy from waste heats. Maximum power is obtained when the connected load to the ends of TEGs matches their internal resistance. However, impedance matching cannot always be ensured. Therefore, TEGs operate at lower efficiency. For this reason, maximum power point tracking (MPPT) algorithms are utilized. In this study, both TEGs and a boost converter with MPPT were modeled together. Detailed modeling, simulation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…MPT occurred at R load of 1-10 Ω [23] Case study N (Park et al, 2014) Showed the use of a low-cost microcontroller and temperature sensor-based circuit, to track TEG MPP with a 1.1% tracking error [24] Case study O (Yildiz et al, 2013) Compared TEG and solar energy conversion. A TEG generates more power relative to solar module of same size but more costly [27] Case study P (Apertet et al, 2014) Deduced that a TEG output power and efficiency in a thermal environment can be simultaneously maximised if its heat flux is constant but not the case if its temperature difference is constant [25] Case study Q (Ebrahimi and Derakhshan, 2018) Proved that a TEC LT-PEM FC hybrid CCHP system is capable of producing 2.79 kW of electricity, 3.04 kW of heat, and 26.8 W of cooling with a total efficiency of~77% and fuel saving of 43.25% [50] Case study R (Mamur and Çoban, 2020)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MPT occurred at R load of 1-10 Ω [23] Case study N (Park et al, 2014) Showed the use of a low-cost microcontroller and temperature sensor-based circuit, to track TEG MPP with a 1.1% tracking error [24] Case study O (Yildiz et al, 2013) Compared TEG and solar energy conversion. A TEG generates more power relative to solar module of same size but more costly [27] Case study P (Apertet et al, 2014) Deduced that a TEG output power and efficiency in a thermal environment can be simultaneously maximised if its heat flux is constant but not the case if its temperature difference is constant [25] Case study Q (Ebrahimi and Derakhshan, 2018) Proved that a TEC LT-PEM FC hybrid CCHP system is capable of producing 2.79 kW of electricity, 3.04 kW of heat, and 26.8 W of cooling with a total efficiency of~77% and fuel saving of 43.25% [50] Case study R (Mamur and Çoban, 2020)…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the cycle is capable of producing 2.79 kW of electricity, 3.04 kW of Figure 16: Influence of thermal environment on optimal working conditions of TEGs (adapted from [27]). [50], the maximum power is attained when the load connected to a TEG matches its internal resistance. However, impedance matching is not always practically guaranteed.…”
Section: Influence Of Thermal Environment On Optimal Workingmentioning
confidence: 99%
See 1 more Smart Citation
“…These multiple maxima are termed local maxima and global maxima [45,46]. Therefore, under NTUD, BMO is required to generate reference voltage for maximizing power/energy output [47][48][49][50].…”
Section: Configuration Of Teg Systemmentioning
confidence: 99%
“…A multi-stage TEC module in cascade was examined in [8]; whereas in [9], an extensive mathematical analyses were articulated for TEG and TEC design and materials. A TEG model was developed in [10] for maximum power point tracking but lacks the detailed underlining maths and the parallel TEG combinations was limited to just 2. A comprehensive TEG and TEC models with the detailed maths supporting the TEG and TEC models, were presented respectively in [11] and [12].…”
Section: Introductionmentioning
confidence: 99%